The Arrangement of the song Nyello' Aeng by Jaka Mahendra Hafizahrawani in the UL – Daul Lancenk Tresna music group, Pamekasan Regency - Louis Andika Budiono (Repertoar, 2026)
The song Nyello' Aeng tells of an activity carried out by villagers who still use or utilize water for their daily needs. The song Nyello' Aeng also tells the story of a village maiden and her activity, Nyello' Aeng, which in Indonesian means "to fetch water." Ul-Daul's musical arrangement of Nyello' Aeng is more interesting and encourages the community to sing along. The presentation is now modern, so the community can clearly hear Nyello' Aeng. The selection of the song Nyello' Aeng for the Ul-Daul musical arrangement was based on the opportunity within the scope of Ul-Daul music. According to Jaka Mahendra, it is rare for Ul-Daul music groups to arrange the song Nyello' Aeng, so Jaka Mahendra wanted to take advantage of this moment to give a new touch to the song Nyello' Aeng.